Perancangan Sistem Pengelolaan Data Akta Kelahiran WNI di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Batu Bara - Fazyra Putri (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
Birth certificate data management is an important aspect of population administration. In the digital era, the need for efficient systems is increasing to overcome various challenges, such as manual errors, slow administrative processes, and difficulties in searching for data. This research focuses on designing a data management system for Indonesian citizens' birth certificates at the Batu Bara Regency Population and Civil Registration Service (Dukcapil). This system was designed using a systematic approach, starting from needs analysis to the implementation stage. The method used involves collecting data through interviews, literature study, and direct observation in the field. The result of this design is a digital-based system that makes it easier to record, store and manage birth certificate data efficiently. By implementing this system, it is hoped that it can improve the quality of public services, minimize data errors, and support the government's digitalization program.